Serum Amyloid A Correlates With the Osteonecrosis of Femoral Head by Affecting Bone Metabolism - Peng, Xiaoyuan; Ma, Yiyang; Wang, Qiyang; Gao, Yanchun; Li, Guangyi; Jiang, Chenyi; Gao, Yun; Feng, Yong (Frontiers in Pharmacology, 2021)
Osteonecrosis of the femoral head (ONFH) is a progressive hip joint disease without disease-modifying treatment. Lacking understanding of the pathophysiological process of ONFH has become the humper to develop therapeutic approach. Serum amyloid A (SAA) is an acute phase lipophilic protein during inflammation and we found that SAA is increased for the first time in the serum of ONFH patients through proteomic studies and quantitatively verified by ELISA. Treating rBMSCs with SAA inhibited the osteogenic differentiation via Wnt/β-catenin signaling pathway deactivation and enhanced the adipogenic differentiation via MAPK/PPARγ signaling pathway activation. Finally, bilateral critical-sized calvarial-defect rat model which received SAA treated rBMSCs demonstrated reduction of bone formation when compared to untreated rBMSCs implantation control. Hence, SAA is a vital protein in the physiological process of ONFH and can be act as a potential therapeutic target to treat ONFH.